2013
DOI: 10.1016/j.dnarep.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Trimming of damaged 3′ overhangs of DNA double-strand breaks by the Metnase and Artemis endonucleases

Abstract: Both Metnase and Artemis possess endonuclease activities that trim 3′ overhangs of duplex DNA. To assess the potential of these enzymes for facilitating resolution of damaged ends during double-strand break rejoining, substrates bearing a variety of normal and structurally modified 3′ overhangs were constructed, and treated either with Metnase or with Artemis plus DNA-dependent protein kinase (DNA-PK). Unlike Artemis, which trims long overhangs to 4–5 bases, cleavage by Metnase was more evenly distributed over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
4
29
2
Order By: Relevance
“…6B). For example, Artemis and Metnase can excise the same 3′phosphoglycolate terminus as Tdp1/PNKP, except when nucleases are used more flanking DNA is lost and the products of excision are heterogeneous [78, 114, 135]. Since damage is removed as part of a patch (i.e.…”
Section: Strategies For Resolving Endsmentioning
confidence: 99%
“…6B). For example, Artemis and Metnase can excise the same 3′phosphoglycolate terminus as Tdp1/PNKP, except when nucleases are used more flanking DNA is lost and the products of excision are heterogeneous [78, 114, 135]. Since damage is removed as part of a patch (i.e.…”
Section: Strategies For Resolving Endsmentioning
confidence: 99%
“…TDP1 removes glycolate residues from 3′ ends followed by additional processing by PNKP to remove the resulting 3′-phosphates (Zhou et al 2009). Recently, Metnase was shown to endonucleolytically trim 3′-overhangs greater than 3 bp on DNA duplexes, although its lack of activity when added to NHEJ-competent extracts casts some doubt on such a role in vivo (Mohapatra et al 2013). The various enzymes involved in the NHEJ pathway have a high flexibility in binding to DNA lesions, allowing them to interact or bind with a plethora of DNA end structures.…”
Section: Non- Homologous End Joining and P53mentioning
confidence: 99%
“…Overall, Metnase exhibits trimming abilities similar to those of Artemis and can act to remove modified bases and blocked termini in some contexts. However, in an extract-based NHEJ model, addition of exogenous Artemis resulted in trimming and subsequent ligation of a DSB with a blocked 3´ overhang, but addition of Metnase did not, even though the same structure was a Metnase substrate as naked DNA [86]. This result casts doubt on a role for Metnase in resolving blocked DSB ends, as it suggests that presence of other NHEJ proteins may hinder rather than promote its endonuclease activity.…”
Section: Metnasementioning
confidence: 55%
“…Mohapatra et al showed that Metnase trims overhangs that terminate in 3´-PGs, and in some cases the 3´-PG stimulated cleavage by Metnase and altered its specificity. However, the presence of a thymine glycol in a short 3´ overhang hindered Metnase's trimming ability in the immediate vicinity of the modified base although it could trim the same modified end in a 7-base overhang [86]. Overall, Metnase exhibits trimming abilities similar to those of Artemis and can act to remove modified bases and blocked termini in some contexts.…”
Section: Metnasementioning
confidence: 94%
See 1 more Smart Citation